MOLLUSKS IN RADIOECOLOGICAL STUDIES OF FRESHWATER ECOSYSTEMS - Гудков, Д.; Дзюбенко, О.; Проценко, О.; Чепіга, Л. (Proceedings of National Aviation University (archive), 2012)
Species-specificity and dynamics of 90Sr, 137Cs and some transuraniс elements accumulation in bivalveand gastropod freshwater molluscs of the Chernobyl exclusion zone during 1998–2010 was analyzed. Theresults of radiation dose as well as chromosome aberration rate estimation and analysis of hemolymphcomposition of molluscs was produced. The radiation absorbed dose rate was registered in the range of 0.3–85.0 μGy h–1. In closed water bodies the heightened chromosome aberration rate (up to 27 %) in embryotissues, and also change of haematological indexes for the adult individuals of snails was registered